Analysis of the dynamics of spiritual values in the context of regional culture (Journal of Philosophy, Culture and Political Science, 2025)
This study is aimed at studying the cultural dynamics of the value system in the southern regions of Kazakhstan. The change in value orientations taking place in modern society is one of the topical issues in the field of cultural studies. The purpose of the study is to analyze the process of transformation of the spiritual value system at the regional level, its causes and consequences, structural features and a comprehensive cultural and social analysis.During the study, an interdisciplinary methodology combining cultural, social and psychological directions, as well as the results of surveys conducted in the southern regions of Kazakhstan and observation data were used as an empirical basis.The results obtained allowed us to systematically study traditional values ​​in modern society, the internal and external factors influencing them, as well as elements of behavior established in national psychology. These are important indicators that affect the cultural integrity of society, social harmony and spiritual stability.The results of the study contribute to understanding internal contradictions in the value system, identifying regional features in the structure of spiritual orientations, and forming effective cultural policy based on these features. The scientific and practical significance of the work lies in the fact that the results obtained can be used in the development of intercultural dialogue, the adaptation of spiritual renewal strategies at the regional level, and the provision of social stability.Keywords: culture, values, spiritual crisis, social factors, cultural transformation, empirical research.